Hormonal abnormalities in alexithymia - Goerlich, Katharina S.; Votinov, Mikhail (Frontiers in Psychiatry, 2023)
Alexithymia is a personality trait characterized by difficulties in emotion recognition and regulation that is associated with deficits in social cognition. High alexithymia levels are considered a transdiagnostic risk factor for a range of psychiatric and medical conditions, including depression, anxiety, and autism. Hormones are known to affect social–emotional cognition and behavior in humans, including the neuropeptides oxytocin and vasopressin, the steroid hormones testosterone and estradiol, the stress hormone cortisol as well as thyroid hormones. However, few studies have investigated hormonal effects on alexithymia and on alexithymia-related impairments in emotion regulation and reactivity, stress response, and social cognition. Here, we provide a brief overview of the evidence linking alexithymia to abnormalities in hormone levels, particularly with regard to cortisol and oxytocin, for which most evidence exists, and to thyroid hormones. We address the current lack of research on the influence of sex hormones on alexithymia and alexithymia-related deficits, and lastly provide future directions for research on associations between hormonal abnormalities and deficits in emotion regulation and social cognition associated with alexithymia.